Numerical study on phase-fitted and amplification-fitted diagonally implicit two derivative Runge-Kutta method for periodic IVPs - Senu, Norazak; Ahmad, Nur Amirah; Ibrahim, Zarina Bibi; Othman, Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2021)
A fourth-order two stage Phase-fitted and Amplification-fitted Diagonally Implicit Two Derivative Runge-Kutta method (PFAFDITDRK) for the numerical integration of first-order Initial Value Problems (IVPs) which exhibits periodic solutions are constructed. The Phase-Fitted and Amplification-Fitted property are discussed thoroughly in this paper. The stability of the method proposed are also given herewith. Runge-Kutta (RK) methods of the similar property are chosen in the literature for the purpose of comparison by carrying out numerical experiments to justify the accuracy and the effectiveness of the derived method.